Depression and cardiovascular disease. Issue 3 (June 2021) - Hare, David L.
Abstract : Purpose of review: The purpose of this review is to outline the relationship between cardiovascular disease (CVD) and depression, both as a cause of and a result of CVD. Recent findings: The prevalence of depression seems to be increasing in the general population. It is likely that depression will be even more of a problem for CVD patients in the post-COVID-19 pandemic era. New studies confirm the independent association of depression with later incident CVD, although perhaps not as strong as suggested by some previous studies. Depression seems to be becoming even more prevalent in CVD patients, with new data for stroke and peripheral arterial disease patients. Cardiologists rarely screen for depression and most do not believe that they have a responsibility for detecting or treating depression. There are new data suggesting that patients who are more in control of their lives have better outcomes and that change is possible. Summary: Depression is preventable and treatable. It is imperative to detect and manage depression in CVD patients. Additional research is required to see whether or not comprehensive patient screening for depression translates into both better quality of life and improved clinical outcomes.